Repeat bronchoalveolar lavage in idiopathic pulmonary fibrosis: proceed with caution?. Issue 5 (27th May 2021) - Jones, Mark G.; Kolb, Martin
Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive fibrosing interstitial lung disease with a median life expectancy of 3–5 years [1]. In recent years, management of IPF has been transformed with the worldwide approval of two anti-fibrotic therapies. In parallel, advances in the understanding of IPF pathogenesis have identified numerous targets for potential therapeutic intervention [2]. However, the adoption of anti-fibrotic therapies as the standard of care for patients with IPF has further increased the complexity of investigating novel therapeutics in clinical trials. New, innovative clinical trial design approaches are therefore being implemented. This includes early-phase trials designed not only to inform about drug dosing, safety and tolerability, but also to provide sufficient confidence on target engagement or potential efficacy to support progression to the much more costly later-phase studies. Careful deliberation is required when considering repeat bronchoalveolar lavage in patients with idiopathic pulmonary fibrosis https://bit.ly/3bMyRfZ